Edukasi Ergonomi dalam Mencegah Gangguan Muskuloskeletal pada Perawat yang Bekerja di Rumah Sakit - Enta, Syafri; Masfuri, Masfuri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between ergonomics education and reducing musculoskeletal disorders for nurses and also to determine appropriate educational methods for nurses working in Hospitals. The research method used was a systematic review by searching for this article using the keywords education, ergonomics, musculoskeletal disorders, and nursing. Inclusion criteria involved nurses working in hospitals, articles with an RCT or clinical trial research design, published within the last 10 years, and interventions that included ergonomics education for nurses. Articles were found through searches in several electronic databases, including PubMed, ProQuest, Science Direct, Scopus, Sage Journal, and Embassy. The research results show that from the 7 articles that have been reviewed, the results of the ergonomics education program have succeeded in reducing the prevalence and risk of musculoskeletal disorders in nursing staff working in hospitals. In addition, there has been a significant reduction in the prevalence of musculoskeletal disorders in various parts of the body. In conclusion, providing ergonomics education to nurses working in hospitals can reduce complaints of work-related musculoskeletal disorders. Keywords: Education, Ergonomics, Musculoskeletal, Nursing.